A preliminary model of the mangrove ecosystem of Dongzhaigang Bay, Hainan, (China) based on Ecopath and Ecospace - Jiang, Chengpu; Pauly, Daniel; Wang, Wenqing; Du, Jianguo; Cheng, Jianhua; Wang, Mao (Frontiers in Marine Science, 2023)
Introduction Marine and coastal ecosystems are complex, especially because of the connection between their many functional groups and the various habitats provided by subsystems. Method To describe the trophic interactions, energy flows, and spatial distribution of species in the ecosystem of Dongzhaigang Bay, in Hainan, China, 28 functional groups were identified, incorporated in Ecopath and Ecospace models, and used to derive the particle size and spatial distribution of the functional groups. Result The results show that the trophic levels of top predators are lower than in similar ecosystems, but that the ecosystem of Dongzhaigang Bay exhibits a high ecotrophic efficiency, leading to a high fraction of its primary and secondary production being transferred to the higher trophic levels. The particle size distribution (PSD; i.e., log(biomass) vs log(particle weight)) in Dongzhaigang Bay, the first estimated for any mangrove ecosystem, has a slope (-0.80) similar to that of other ecosystems along China’s coast , but does not include the largest size groups. Ecospace allowed a visualization of the functional groups in Dongzhaigang Bay, which can serve as a basis, e.g., for identifying areas requiring special protection. Discussion Though the status of the bay, overall, appears to be better than many of the Chinese coastal ecosystems, further monitoring and data collection are required to deepen the understanding of the interactions within the ecosystems, and the impacts of human activities on Dongzhaigang Bay. The models presented here should help in this undertaking.